Health Care Utilization - MIDWEST SAPH 2018 (University of Minnesota Libraries Publishing, 2018)
Faculty Discussant: A. Simon Pickard, PhD Article 1: Real-World Cost-Effectiveness Analysis of Allogeneic Hematopoietic Stem Cells Transplantation vs. Hydroxyurea Therapy in Children with Sickle Cell Disease Jifang Zhou, MD, MPH; Gregory S. Calip, PharmD, MPH, PhD Article 2: Fondaparinux Sodium Compared with Low Molecular Weight Heparins for Thromboprophylaxis among the Patients with Orthopedic Immobility: A Systematic Review and Meta-Analysis Arun Kumar PharmD, MS; Ashna Talwar, BPharm; Wenchen Wu, PhD; Joel F Farley, PhD Article 3: Differences by Primary Insurance in 30-day All-cause Readmission for Patients Undergoing Breast Cancer Surgeries Ming Chen, MS, MSPharm; Shelley Irene White-Means, PhD, MA; Sam Li, PhD, MS Article 4: Seasonal Variation in Heart Failure Hospitalizations in the United States Kendra Y. Foster, MS; Linnea A. Polgreen, PhD Article 5: Antidiabetic Medications among People 20 years and Older and with Diabetes in the United States Julie Zhiying Zhao, MPH; Angeline Carlson, PhD Article 6: Healthcare Utilization in Type 2 Diabetes Patients Using DPP-4 inhibitors and GLP-1 Agonists Sajan Pandya BPharm; Monica Hwang, PhD Article 7: Estimating the Impact of the Food and Drug Administration's (FDA) Unapproved Drug Initiative (UDI) on Drug Prices and Expenditures Sharma D; Schumock GT; Saffore C; Edwards SA; Walton SM